Perancangan Aplikasi Kesehatan Mental â€œNAFSâ€ (Islamic Psycho Spiritual Therapy) Berbasis Android Menggunakan Metode PDCA (Plan-Do -Check-Action) - Ross, Hanna Oktasya; Arrohmah, Aulia Syifa; Hasanah, Megawatul; Yusran, Naufal; Wijareni, Nurastuti (Teknik Informatika Universitas Pamulang, 2021)
During the Covid-19 pandemic, the percentage of mental disorders has increase significantly. This increase is not comparable to the available services or handling media, especially the Indonesian people, who are predominantly Muslim. In fact, mental health is an important aspect of human life. Therefore, the design of the NAFS application is based on Islamic psychology (Islamic psycho-spiritual therapy) which can be an innovation for android-based mental health services. NAFS Application Design is carried out using the PDCA method with a participatory design. The results of all the design stages can be concluded that the NAFS application based on alpha (black box method) and beta testing shows its functionality and performance in accordance with the needs and designs that have been determined. Thus it can be concluded that the NAFS application can be used especially for individuals with mental illness, as a form of mental health first aid and mental health education media.